Present state of power electronics circuitry and perspectives of its development - Sokol, Yevgen I.; Goncharov, Y. P. (Національний університет "Львівська політехніка", 2011)
This paper is devoted mainly to the circuitry, because element base is a big independent issue. Let us say a few words about terminology. A modern converter can be rarely represented as a simple device like “rectifier”, “inverter” etc. It usually consists of the combination of several units, performing elementary functions. For such multistage units it makes sense to use a definition of converter “technology”, keeping in mind some actions with electric current for a certain purpose. It is similar to the step activities in chemistry: to take a substance, to heat it etc. After the formulation of a goal and a number of necessary actions it is possible to present a corresponding structure circuit. According to described above we tried to mention basic technologies used in modern power electronics. The perspectives of the electronics in the nearest future are connected with the further improvement of basic technologies, because their combination allows for developing new technologies. In our opinion, there are four such technologies.

Стаття присвячена проблемам схемотехніки у сучасній енергетиці. Розглянуто декілька напрямків розробок електроприводів, відмічено їхні переваги та недоліки. Описано сучасні схемотехнічні можливості та перспективні напрямки їхнього подальшого розвитку в Україні.
Keywords: power electronics; technology; Ukraine